Ecologies of learning, visual narratives and ethnography. Metholodogical notes about Universidad Rural Paulo Freire case. - Cortés-González, Pablo; Márquez-García, María Jesús (My University, 2016)
In this paper we present some of the first methodological results of the R&D Project called "Ecologies of learning in multiple contexts: analysis of expanded education projects and citizenship configurations" funded by Minister of Economy and Competitiveness (Spain) . The interest of this project arises after considering that much of the individual and organizational learnings have been turning invisible in the different educational spaces. Therefore, our purpose is to study the different socio-educational mechanisms that individuals and organizations put into play in differents scenarios: schools, asociations, virtual academical contexts, etc. On this ocassion, we present some of the methodological aspects from a rural environment, especifically the study we are developing with ‘Universidad Rural Paulo Freire’ of the Ronda mountain range (onwards URPF). This organization is focused in the recovery of tradicional learnings that people used to have around the rural world. At the same time, they are settled in a critical perspective that connects their actions with approaches of sustainability, dignity, feminims, etc. The general objetives we consider for this project are the following: 1) To know life style of people in Ronda mountain range context. 2) To understand the configuration of URPF group and its impact in the territory. 3) To promote learning communities of practice with other organizations. In order to draw on these general porpuses and after an agreement process with the URPF collective, we designed methodologically the develop of life stories, visual narratives and a deep narrative ethnography.
Keywords: Etnología; Educación intercultural; Etnografía; Educación rural; Metodología